Influência da gordura subcutânea de novilhos terminados em confinamento nas características de carcaça e carne - Boito, Bruna (2014)
This study was develop to evaluate the carcass characteristics,quality and lipid profile linked to subcutaneous fat thickness (SFT) using the slaughter weight as a co-variable. The data were analyzed by statistical test for analysis of variance with a 10% level of significance, and subsequently made the regression analysis for the variables that showed significant differences. The carcass and meat quality was influenced by the subcutaneous fat thickness interfering in the hot and cold carcass weight, and consequently on their yields. The hot carcass weight (HCW) was the principal form of remuneration to farmers for slaughterhouses, applying values of 6 mm of subcutaneous fat thickness in an animal that was slaughter with weight of 450 kg in equation (HCW = 23,77+0,60*SW+1,99*FT+0,32*FT²), shows the value of 269.69 kg of hot carcass weight and cold carcass weight (CCW) using the same values in equation (CCW =-11,86+0,56*SW+1,64*FT), the animal had presented averaged 249.98 kg of CCW. There were significant differences for the portions of the animal tissue with decreased bone fraction and increased muscle and fat fractions, as increased the subcutaneous fat thickness in the carcass. For the organoleptic quality of meat, there were no significant responses for the different subcutaneous fat thickness level. In the analyzes of the lipid profile, the saturated fatty acids (SFA) do not change with increasing thickness of carcass fat, unlike the unsaturated fatty acid (UFA), which increased quadratically to the point of 5.8 mm fat thickness. The IFA were divided into monounsaturated (MUFA) and polyunsaturated fats, polyunsaturated occurred for linear significant difference decreasing. Monounsaturated responded quadratically (AGM = 14,27+0,037*SW+4,22*FT-0,31*FT²). Among the major fatty acids found in beef cattle, C14: 0 showed no significant difference as well as the fatty acid C18: 0. Have the C16: 0 present a significant difference (P = 0.0095) showing 6.6 mm SFT as the maximum point. The isomer C18: 1ω9c important in the synthesis of CLA obtained quadratic comportment present a maximum value of 6 mm SFT. The CLA obtained quadratic response, its concentration increases up to 6.9 mm subcutaneous fat thickness, after this fat thickness the CLA values begin to decline. The ratio between the fatty acids ω6:ω3 did not show different significance. The 3 obtained quadratic response, increase your deposition up to 6.3 mm of fat thickness, this value starts declining after interfering in good relationship between ω6: ω3. The fat thickness of 6.0 mm has positively influence in the weight and yield of hot and cold carcass, the amount of bone, muscle and fat present in the animal carcass and influences the beneficial fatty acids for human health.